WORKSHOP PEMANFAATAN AIR KELAPA HIJAU (cocus nucifera) SEBAGAI MEDIA IDENTIFIKASI ALTERNATIF TRIPLE SUGAR IRON AGAR (TSIA) UNTUK PERTUMBUHAN BAKTERI Escherichia coli - Siregar, Sa’adah; Vincentia, Vincentia; Bintang, Siti Sarah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Bacterial growth media is a material consisting of a mixture of nutrients that are used by bacteria to grow and reproduce. Biochemical tests are carried out to see the characteristics of bacteria through biochemical reactions, which are usually carried out including TSIA (Triple sugar iron agar) media which is used to identify gram-negative rod bacteria to see their ability to ferment glucose, sucrose and lactose. Based on the potential nutritional content of green coconut water, green coconut water is rich in nutrients such as potassium, protein, carbohydrates in the form of suxora (disaccharides), glucose, fructose (monosaccharides) in green coconut water, which are monosaccharides that are more easily utilized for growth as prebiotics. This type of research is experimental research. Objective: laboratory scale where this research will look at the growth of bacteria using green coconut water (Cocus Nucifera) as an alternative medium to replace Triple Sugar Iron Agar (TSIA) media. The results of the research show the growth of Escherichia coli bacterial colonies on the media. Conclusion: Green coconut water resulted in good bacterial growth. Based on the results of research on differences in the growth of Escherichia coli bacteria on TSIA (Triple Sugar Iron Agar) media and on alternative media of green coconut water (Cocus nucifera), it can be concluded that Green coconut water media can be used as an alternative medium for cultivating Escherichia coli bacteria as a substitute for TSIA.